2023
DOI: 10.3389/fimmu.2023.1190841
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 7 in inflammation, cancer and infection

Abstract: Interferon regulatory factor 7 (IRF7), a member of the interferon regulatory factors (IRFs) family, is located downstream of the pattern recognition receptors (PRRs)-mediated signaling pathway and is essential for the production of type I interferon (IFN-I). Activation of IRF7 inhibits various viral and bacterial infections and suppresses the growth and metastasis of some cancers, but it may also affect the tumor microenvironment and promote the development of other cancers. Here, we summarize recent advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…In line with Fasolino et al. ( 20 ) observations, we report that the duct-acinar subpopulation expresses, although at low levels, ICAM1, ISG20, and IRF7, which are essential for immune cell interaction and the promotion of inflammation ( 31 33 ).…”
Section: Discussionsupporting
confidence: 90%
“…In line with Fasolino et al. ( 20 ) observations, we report that the duct-acinar subpopulation expresses, although at low levels, ICAM1, ISG20, and IRF7, which are essential for immune cell interaction and the promotion of inflammation ( 31 33 ).…”
Section: Discussionsupporting
confidence: 90%
“…The regulatory factors interferon IRF1 and IRF7 are known to regulate the expression of interferons of the first (α and β) and second (γ) types, acting as inducers of inflammation in the development of tumor diseases [ 32 , 33 , 34 ]. STAT3 and STAT6 are also known to be activated during inflammation in the tumor microenvironment; their activity may be associated with an increased inflammatory response during leukemia progression [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…IRF7 is a lymphoid-specific factor that is predominantly expressed in the cytoplasm of the spleen, thymus and peripheral blood lymphocytes, such as B cells, plasmacytoid dendritic cells (pDCs) and monocytes ( Ma et al, 2023 ). Recent studies have revealed that IRF7 exerts a broad range of activities in different biological processes ( Qing and Liu, 2023 ). In this study, YP significantly reduced the mRNA level of IL-1β in jejunum and ileum compared with PEDV group, this is consistent with the study of No et al (2021) .…”
Section: Discussionmentioning
confidence: 99%